Hydrogen-peroxide synthesis and LDL-uptake controls immunosuppressive properties in monocyte-derived dendritic cells - Menzner, Ann-Katrin; Rottmar, Tanja; Bosch, Jacobus J.; Mougiakakos, Dimitrios; Mackensen, Andreas; Resheq, Yazid; Völkl, Simon (Cancers, 2021)
Given the encouraging success of immunotherapy in cancer, the role of metabolism in tumor immune-evasion is an emerging research field with a unique potential to overcome current limitations in immunotherapy. Herein, hepatic stromal cells, which may act as immunological bystanders in cancer, are capable of inducing immunosuppressive phenotypes in monocytic cells by controlling hydrogen peroxide (H2O2-) metabolism. As monocytic cells play an important role in tumor-immunology, we sought to identify the underlying mechanisms. Herein, we unraveled a complex interaction between cholesterol/LDL- and H2O2-metabolism: Extracellular depletion of H2O2 leads to enhanced H2O2-production with a consecutive increase in LDL-uptake throughout differentiation of monocytes to monocyte-derived dendritic cells and, as a result, to the induction of distinct immunosuppressive properties. These findings shed new light on the role of LDL-metabolism in tumor-immunology and might help to further improve immunotherapeutic approaches against cancer. Background and Aims: Induction of myeloid-derived suppressor cells (MDSC) is a critical step in immune cell evasion by different cancer types, including liver cancer. In the liver, hepatic stromal cells orchestrate induction of MDSCs, employing a mechanism dependent on hydrogen peroxide (H2O2) depletion. However, the effects on monocyte-derived dendritic cells (moDCs) are unknown. Methods: Monocytes from healthy donors were differentiated to moDCs in the presence of extracellular enzymatic H2O2-depletion (hereinafter CAT-DCs), and studied phenotypically and functionally. To elucidate the underlying molecular mechanisms, we analyzed H2O2- and LDL-metabolism as they are interconnected in monocyte-driven phagocytosis. Results: CAT-DCs were of an immature DC phenotype, particularly characterized by impaired expression of the costimulatory molecules CD80/86. Moreover, CAT-DCs were able to suppress T-cells using indoleamine 2,3-dioxygenase (IDO), and induced IL10/IL17-secreting T-cells-a subtype reported to exert immunosuppression in acute myeloid leukemia. CAT-DCs also displayed significantly increased NADPH-oxidase-driven H2O2-production, enhancing low-density lipoprotein (LDL)-uptake. Blocking LDL-uptake restored maturation, and attenuated the immunosuppressive properties of CAT-DCs. Discussion: Here, we report a novel axis between H2O2- and LDL-metabolism controlling tolerogenic properties in moDCs. Given that moDCs are pivotal in tumor-rejection, and lipid-accumulation is associated with tumor-immune-escape, LDL-metabolism appears to play an important role in tumor-immunology.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Catalase; Hydrogen peroxide; IDO; LDL-uptake; Reactive oxygen species; Tolerogenic dendritic cells; Tumor immune escape